Surface Enhanced Raman Spectroscopy with La0.5Bi0.5FeO3-Based Substrates for Paraquat Pesticide Detection - Tiawati, Nia; Triyono, Djoko; Shiddiq, Muhandis (Diponegoro University Semarang Indonesia, 2025)
Paraquat is a highly toxic herbicide that poses serious environmental and health risks. Conventional detection methods are accurate but often complex and time-consuming. This study explores the use of La0.5Bi0.5FeO3 (LBFO) perovskite as a novel Surface-Enhanced Raman Spectroscopy (SERS) substrate. LBFO was synthesized via a sol-gel method and characterized using XRD, XRF, UV-Vis, and Raman spectroscopy. The LBFO-based substrate successfully enhanced the Raman signals of paraquat, enabling detection at concentrations as low as 6 ppm. These results suggest the feasibility of LBFO as an effective and low-cost SERS substrate for rapid paraquat detection.